Analysis of the Impact of Exports And Imports on Indonesia's Economic Growth: A Study For the Period 2014–2023 - Rita Saragi; Sanusi Ghazali Pane (International Forum of Researchers and Lecturers, 2025)
This research aims to examine the influence of exports, imports, and exchange rates on Indonesia's economic growth during the 2014–2023 period. The study employs a multiple linear regression approach using SPSS version 26 for data analysis. The findings reveal that exports, imports, and exchange rates collectively exert a significant impact on economic growth. Individually, exports contribute positively and significantly, while both imports and exchange rates show a significant negative effect on Indonesia’s GDP. These outcomes align with Keynesian economic theory, which emphasizes exports as a critical component in boosting aggregate demand and stimulating growth. Meanwhile, the negative influence of imports and exchange rates supports the Heckscher-Ohlin model and the Purchasing Power Parity (PPP) theory, indicating that excessive reliance on imports and currency depreciation can undermine domestic economic performance. This study, therefore, highlights the importance of robust trade policies and stable exchange rates to foster sustainable national economic growth.